Synthesis of Axially Chiral Biaryls via Enantioselective Ullmann Coupling of ortho‐Chlorinated Aryl Aldehydes Enabled by a Chiral 2, 2′‐Bipyridine Ligand. (21st October 2022) - Perveen, Saima; Zhang, Shuai; Wang, Linghua; Song, Peidong; Ouyang, Yizhao; Jiao, Jiao; Duan, Xin‐Hua; Li, Pengfei
Abstract: The first nickel‐catalyzed highly enantioselective reductive Ullmann coupling of ortho ‐chlorinated aryl aldehyde was achieved under mild reaction conditions with a chiral 2, 2′‐bipyridine ligand (+)‐DTB‐SBpy, thus providing axially chiral biphenyl or binaphthyl dials with up to 99 % yield and 99.5:0.5 er. The versatility of the products as common synthetic intermediates for diverse axially chiral ligands, catalysts, and functional molecules was demonstrated by short‐step transformations. This protocol also allowed the concise and highly enantioselective formal total synthesis of biologically active natural products (+)‐kotanin, (−)‐isoschizandrin and (+)‐gossypol. Abstract : Reported is a general and highly enantioselective Ni‐catalyzed reductive homocoupling of ortho ‐chlorinated aldehydes enabled by a SBpy‐type chiral 2, 2′‐bipyridine ligand. This mild and step‐economical approach allowed the synthesis of various axially chiral biaryl dials, and also provided versatile intermediates for diverse axially chiral catalysts, ligands, and natural products.